2012
DOI: 10.1038/jp.2012.81
|View full text |Cite
|
Sign up to set email alerts
|

Obesity during pregnancy and fetal iron status: is Hepcidin the link?

Abstract: Objective To ascertain the effect of obesity-related inflammation on maternal and fetal iron status. We hypothesized that obese pregnant women would have increased inflammation, hepcidin levels, and that their infants would have impaired iron status compared to lean controls. Study Design Fifteen obese (Ob) and fifteen lean (Lc) women were recruited in their second trimester of pregnancy. Markers of iron status, inflammation and hepcidin were measured in maternal and cord blood. Student’s t test was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
118
6
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(139 citation statements)
references
References 19 publications
12
118
6
3
Order By: Relevance
“…Of note, Tussing-Humphreys et al (46) found substantially higher serum hepcidin and CRP, together with lower iron status in obese versus lean women. Similar results were reported in other adult cohorts, as well as children (53,55,57), and pregnant women (54). As to the latter, we recently found higher hepcidin and CRP levels in obese pregnant women compared with lean pregnant women (54).…”
Section: Current Status Of Knowledgesupporting
confidence: 75%
See 3 more Smart Citations
“…Of note, Tussing-Humphreys et al (46) found substantially higher serum hepcidin and CRP, together with lower iron status in obese versus lean women. Similar results were reported in other adult cohorts, as well as children (53,55,57), and pregnant women (54). As to the latter, we recently found higher hepcidin and CRP levels in obese pregnant women compared with lean pregnant women (54).…”
Section: Current Status Of Knowledgesupporting
confidence: 75%
“…Similar results were reported in other adult cohorts, as well as children (53,55,57), and pregnant women (54). As to the latter, we recently found higher hepcidin and CRP levels in obese pregnant women compared with lean pregnant women (54). Iron status markers did not differ between the mothers, but they did for the newborns, with lower transferrin saturation (Tsat) and serum iron in cord blood from the obese group.…”
Section: Current Status Of Knowledgesupporting
confidence: 72%
See 2 more Smart Citations
“…Maternal obesity disrupts iron transfer to the fetus owing to the increase in the level of hepcidin, in particular, and to the effect of a pro-inflammatory medium. Due to these changes, anemia often occurs in maternal obesity (57). …”
Section: Introductionmentioning
confidence: 99%